Recent advances in infrared laser lithotripsy [Invited] - Fried, Nathaniel M. (Biomed Opt Express, 2018)
The flashlamp-pumped, solid-state, pulsed, mid-infrared, holmium:YAG laser (λ = 2120 nm) has been the clinical gold standard laser for lithotripsy for over the past two decades. However, while the holmium laser is the dominant laser technology in ureteroscopy because it efficiently ablates all urinary stone types, this mature laser technology has several fundamental limitations. Alternative, mid-IR laser technologies, including a thulium fiber laser (λ = 1908 and 1940 nm), a thulium:YAG laser (λ = 2010 nm), and an erbium:YAG laser (λ = 2940 nm) have also been explored for lithotripsy. The capabilities and limitations of these mid-IR lasers are reviewed in the context of the quest for an ideal laser lithotripsy system capable of providing both rapid and safe ablation of urinary stones.